Proposed Law for the European Health Data Space in Context - Křepelka, Filip (Medicine, Law & Society, 2023)
Analysing electronic health records could improve medicine, but personal data protection impedes this research. The European Health Data Space shall unleash these data. The focus now shifts on how best to balance this effort while at the same time protecting patients' privacy and autonomy. Still, we need to address the reality. Research on images, laboratory results and prescriptions will be easy, as they are electronic. However, the written core of health records is not structured, and establishing summaries for all patients is challenging. Regulations instead of directives are a laudable solution to help simplify the situation. Nonetheless, new challenges emerge with the co-existence of supranational and national frameworks if the former is to have far-reaching ambitions.